The Calcium Wave Model of the Perception-Action Cycle: Evidence from Semantic Relevance in Memory Experiments - Pereira Jr, Alfredo; Santos, Rafael P.; Barrros, Rafael F. (Frontiers in Psychology, 2013)
We present a general model of brain function (the calcium wave model), distinguishing three processing modes in the perception-action cycle. The model provides an interpretation of the data from experiments on semantic memory conducted by the authors.